Evaluation of indoor air pollution in traditional bazaars- Case study in Naqsh-e-Jahan square of Isfahan in 2018-2019 - Arezoo Tavakoli (Mashhad University of Medical Sciences, 2020)
Background and Aim: Air quality in indoor environments such as shopping places is affected by vehicles, in consequence of vicinity with streets and overcrowding. Despite the effect of air pollutants on community health, less attention has been paid to air pollution in traditional bazaars with natural ventilation. The aim of this study is to evaluate concentration of some air pollutants in three traditional bazaars (Sarai-e-Mokhles, Ghanadiha and Ghahvehkashiha) in Isfahan, placed at the Naqsh-e-Jahan Square. Materials and methods: The concentration of SO2, NO2, O3, Particulate Matters (PM2.5 & PM10) were determined by Aeroqual S500 using a direct assay method. The population of fungi and bacterial were determined by Flite 3 sampling pump (SKC) during a nine-month period from autumn 2018 to spring 2019.  Results: Based on results, the pollutant concentrations were much higher at the end of the weeks. In all stations, O3 concentration was close to zero but the concentrations of SO2, NO2, PM2.5 and PM10 demonstrated higher concentrations than that of the standards. The air quality in Sarai-e-Mokhles and Ghanadiha are more critical than Ghahvehkashiha. The gram-positive Bacillus and Penicillium sp were the most population of bacteria and fungi, respectively. Conclusion: The lack of a ventilation system, various occupational activities, as well as the traffic of motorcycles increased the concentration of pollutants in the bazaars. Based on the long-term presence of market shopkeepers and high people density, it is necessary to pay more attention to air quality and to provide solutions to reduce air pollutant concentrations.